2016
DOI: 10.4236/ojoph.2016.64028
|View full text |Cite
|
Sign up to set email alerts
|

Lower Lid Entropion Secondary to Missed Intraorbital Foreign Body in a Child

Abstract: Background: Intraorbital foreign bodies can result in various complications if not appropriately managed. Aim: To report a case of lower lid entropion secondary to a missed intraorbital foreign body. Case Presentation: A 7-year-old boy presented with inward turning of the left lower lid for three days prior to admission. A week before, the child was in the garden when part of the roof of their home suddenly broke off, with pieces of the debris falling near him. He complained of left eye irritation, but a visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…According to our findings, the eyelids should be searched first, followed by the conjunctival fornix, and if the foreign body is located in the posterior orbit, the entry wound could be on the sclera or cornea, and a double perforation of the ocular globe may be present (18). Regarding the clinical signs associated to IOFBs, the most frequent are optic nerve lesion, limitation of ocular motility, exophthalmia and infection (21). Our study is the first to have identified statistically significant factors influencing the clinical signs of a foreign body.…”
Section: █ Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…According to our findings, the eyelids should be searched first, followed by the conjunctival fornix, and if the foreign body is located in the posterior orbit, the entry wound could be on the sclera or cornea, and a double perforation of the ocular globe may be present (18). Regarding the clinical signs associated to IOFBs, the most frequent are optic nerve lesion, limitation of ocular motility, exophthalmia and infection (21). Our study is the first to have identified statistically significant factors influencing the clinical signs of a foreign body.…”
Section: █ Discussionmentioning
confidence: 86%
“…The same tendency was observed in extraconal compared to intraconal foreign bodies. While metallic foreign bodies except for copper are well tolerated if the globe is not injured (18), the organic foreign bodies, especially wooden ones, are linked to a high risk for bacterial and fungal infections, inflammatory granuloma formation, and calcification (21,22). In our series, nonmetallic foreign bodies, mostly wooden, were more aggressive than the metallic foreign bodies, leading to a higher prevalence of clinical signs such as palpebral edema, upper lid ptosis, and displacement of the eyeball.…”
Section: █ Discussionmentioning
confidence: 99%